PENINGKATAN KETERAMPILAN MENULIS TEKS ANEKDOT DAN PRESTASI BELAJAR BAHASA INDONESIA DENGAN METODE INKUIRI PESERTA DIDIK KELAS X IPA 1 SMAN 3 METRO - Susnelly Susnelly (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
The research objective was to describe the writing skills of anecdotal texts using the inquiry method for students of Science class X.1 State Senior High School 3 Metro. The research design used was classroom action research, including observation, documentation, and interviews. Techniques and collections in the form of test and non-test data. The results showed an increase in pre-cycle anecdotal text writing skills to the first cycle, the total percentage was 47.38%, and the average learning achievement of students in pre-cycle 46, in the first cycle to 66, increased by 20%. The increase in the percentage of anecdotal text writing skills in cycle II was 97.68%. When compared with the first cycle of 47.38% to the second cycle of 97.68%, there was an increase of 50.30%. In the third cycle, the improvement of anecdotal text writing skills was 65.69. In the third cycle the average anecdotal text writing skill score was 85, an increase of 10%. Thus, the Inquiry method can improve the skills in writing anecdotal texts.